Cytopathological and immunocytochemical findings of pancreatic anaplastic carcinoma with ZEB1 expression by means of touch imprint cytology. Issue 2 (23rd September 2017) - Naito, Yoshiki; Kawahara, Akihiko; Taira, Tomoki; Takase, Yorihiko; Murata, Kazuya; Ishida, Yusuke; Okabe, Yoshinobu; Tanigawa, Masahiko; Mihara, Yutaro; Nakayama, Masamichi; Shimamatsu, Kazuhide; Yano, Hirohisa; et al.
Abstract : Pancreatic anaplastic carcinoma (PAC) is rare and has an aggressive clinical course. We report an autopsy case of PAC focusing on the cytopathological characteristics of the tumor and immunocytochemical staining for vimentin, E‐cadherin, and zinc finger E‐box binding homeobox 1 (ZEB1), which markers are associated with epithelial markers of epithelial‐mesenchymal transition (EMT). A 50‐year‐old woman presented to our hospital with a chief complaint of jaundice. A pancreatic head tumor and multiple liver nodules were detected on abdominal computed tomography. Biliary cytology under endoscopic retrograde cholangiopancreatography suggested ductal adenocarcinoma. Three months after admission, she died of multiorgan failure. At autopsy, touch imprint cytology using squash preparation of the pancreatic tumor identified two different cell types; numerous isolated malignant cells with large and pleomorphic nuclei and a few clusters showing irregularly overlapped nuclei and irregular contours within the necrotic background. Immunocytochemically, isolated cells were positive for vimentin and ZEB1, and negative for E‐cadherin. Conversely, clusters were negative for vimentin and ZEB1, and positive for E‐cadherin. Histologically, the tumor was composed of sarcomatous cells with small foci of adenocarcinoma, which were consistent with a diagnosis of PAC. Immunohistochemical staining of the adenocarcinoma and sarcomatous cells corresponded to those of the clusters and isolated malignant cells, respectively. Immunostaining of these EMT markers is useful to distinguish sarcomatous cells from adenocarcinoma and can contribute to the accurate diagnosis of pancreatic tumors with EMT.